Potensi Antihiperpigmentasi Daun Michelia Alba: Studi In Silico - Felysia Isman; Paundra Rizky Pratama; Wahida Annisa Ermadayanti; Cici Muarifah; Arif Fadlan (Fakultas Farmasi Universitas Setia Budi, 2022)
Michelia alba empirically provides a youthful effect associated with the formation of melanin or skin pigment by tyrosinase enzyme. However, the excessive formation of melanin results in hyperpigmentation and various dermatological disorders such as freckles, melasma, and age spots. Synthetic antihyperpigmentations, which suppress melanin production, have been widely used, but have shown adverse side effects. This study aims to examine the potential of M. alba as a natural antihyperpigmentation agent. The in-silico research was conducted on the compounds contained in M. alba leaves through molecular docking against tyrosinase enzyme (PDB ID: 1BUG) followed by analysis of physicochemical properties and absorption, distribution, metabolism, excretion, and toxicity profiles (ADMET). The molecular docking results of cis-linalool oxide, trans-linalool oxide, linalool, β-elemene, α-humulene, and nerolidol in M. alba leaves against 1BUG indicated that nerolidol, α-humulene, and β-elemene showed lower docking scores than kojic acid and hydroquinone as controls. Nerolidol, α-humulene, and β-elemene interacted with 1BUG via hydrogen bonding, Van der Walls, and alkyl/π-alkyl and π-π stacking interactions. All compounds did not violate Lipinski and Veber rules based on the analysis of physicochemical properties. All compounds also had good absorption, distribution, metabolism, excretion, and toxicity profiles based on the parameters in each of these evaluations in the ADMET analysis.